2018
DOI: 10.4236/wjcd.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Role of CIMT, eGFR, and Serum HbA1c in Predicting CAD in Non-Diabetic Patients Undergoing Elective Coronary Angiography

Abstract: Background: Pre-diabetic state, renal function, atherosclerosis burden are the major predictors for development of coronary artery disease (CAD). Present study aims to analyze the role of carotid intima-media thickness (CIMT), glomerular filtration rate (eGFR) and serum glycosylated hemoglobin (HbA1c) levels in predicting CAD on coronary angiography in non-diabetic patients. Methods: CAD and its severity according to SYNTAX score (SX score) was evaluated in 450 non-diabetic patients hospitalized with acute cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…In contrast to our study, Kapil et al revealed a positive predictor relationship between HbA1c and cardiovascular disease (p=0.001) [1]. Moreover, another study from North Eastern India, which used the SYNTAX score also reported a highly significant correlation between elevated HbA1c and higher SYNTAX score [12].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our study, Kapil et al revealed a positive predictor relationship between HbA1c and cardiovascular disease (p=0.001) [1]. Moreover, another study from North Eastern India, which used the SYNTAX score also reported a highly significant correlation between elevated HbA1c and higher SYNTAX score [12].…”
Section: Discussioncontrasting
confidence: 99%
“…- Additional markers, such as coronary intima-media thickening, glomerular filtration rate (GFR), microalbuminuria, and serum creatinine, should be considered, as they have been successful in pointing toward severe coronary diseases. Carotid intima-media thickness (CIMT) is considered a marker for early atherosclerosis disease, allowing detection in the subclinical stage [1]. Further, microalbuminuria is found to be a strong predictor of the presence and severity of CAD [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation